Standardization of resin and hardener mixing conditions for optimal preservation of dried flowers - KHARWAL, DIKSHA; KUMARI, POONAM (Journal of Ornamental Horticulture, 2025)
The present study was conducted in the Agrotechnology division laboratory of CSIR-IHBT, Palampur, during 2024 to determine the optimal conditions embedding dried flowers in epoxy resin products. A completely randomized design with twelve treatments and three replications were used. Fresh hydrangea flowers were dried using silica gel and borax desiccants, and then embedded in an epoxy resin and hardener mixture at a 3:1 ratio. The mixture was subjected to various mixing conditions and then poured into molds with the flowers and left to set at room temperature. Setting times under different temperatures and durations were evaluated, along with qualitative assessments using a 5-point hedonic scale for various parameters. Results indicated that temperature and mixing duration did not significantly affect the setting time. The longest setting time of 25.05 hours was observed for treatment T4 (mixing in HWB at 40? for 5 minutes), while the shortest setting time of 17.00 hours was recorded for treatment T10 (mixing at room temperature for 21 minutes). Qualitative analysis demonstrated that these treatments influenced the color, texture, brittleness, contrast, transparency, aesthetic beauty and overall acceptability of the resin products. The best transparency (4.13) and overall acceptability (3.13) were achieved with treatment T4.